Identification Of Forensic Case Using Molecular Markers: A Case Study Of Hyaena (Hyaena Hyaena) - RANJANA BHASKAR,; IMRAN KHAN,; SURENDRA PRASAD GOYAL, (International Journal of Pharma and Bio Sciences, 2011)
We describe a recent case in which an animal was killed, burnt and body parts were sent to the Institute for identifying species and the method used for extracting DNA from burnt tissues. Two mitochondrial gene cytochrome b and 16s rRNA were used for species identification. Sequence analysis revealed that the burnt sample was of a Hyaena (Hyaena hyaena), a Schedule III animal according to the Wildlife (Protection) Act 1972 of the Government of India.